The ubiquitous nuclear protein, NHP1, binds with high affinity to different sequences of the chicken vitellogenin II gene. - Hughes, M J (1989)
In gel shift assays, affinity chromatography-purified NHP1 forms a stable complex with different sequences of the chicken vitellogenin II gene. The apparent KD of NHP1 with the estrogen response element (ERE) containing 5-methylcytosine is 1 X 10(-11) M. NHP1 does not form a complex with the Xenopus vitellogenin ERE where the GCG bases are replaced by CAG. NHP1 is closely related if not identical to the other ubiquitous proteins NHP2, NHP3 and NHP4 that bind specifically to different sequences. All four proteins behave identically on chromatography and give identical patterns in proteolytic bandshift assays. NHP1, NHP2 and NHP3 have a native molecular weight of 170,000 and are composed of two polypeptides of 85 and 75 kDa. The possible function of NHP1 is discussed.